Auditory brainstem responses are resistant to pharmacological modulation in Sprague Dawley wildtype and Neurexin1α knockout rats - Marashli, Samuel; Janz, Philipp; Redondo, Roger L. (bioRxiv beta, 2023)
Sensory processing in the auditory brainstem can be studied with auditory brainstem responses (ABRs) across species. Although ABRs have been widely utilized to evaluate abnormalities in auditory brainstem physiology, there is limited understanding if ABRs can be useful tool to assess the effect of pharmacological interventions. Therefore, we set out to understand how pharmacological agents that target key transmitter systems of the auditory brainstem circuitry affect ABR physiology in rats. Given previous studies, demonstrating that Nrxn1α KO Sprague Dawley rats show substantial auditory processing deficits and altered sensitivity to GABAergic modulators, we used both Nrxn1α KO and wildtype littermates in our study. First, we probed how different commonly used anesthetics (isoflurane, ketamine/xylazine, medetomidine) affect ABRs waveforms. In the next step, we assessed the effects of different pharmacological compounds (diazepam, gaboxadol, retigabine, nicotine, baclofen and bitopertin) either under isoflurane or medetomidine anesthesia. We found that under our experimental conditions, ABRs are largely unaffected by diverse pharmacological modulation. Significant modulation was observed with i.) nicotine, affecting the late ABR components at 90 dB stimulus intensity under isoflurane anesthesia in both genotypes, and ii.) retigabine, showing a slight decrease in late ABRs deflections at 80 dB stimulus intensity, mainly in isoflurane-anesthetized Nrxn1α KO rats. Our study suggest that ABRs in anesthetized rats are resistant to a wide range of pharmacological modulators, which has important implications for the applicability of ABRs to study auditory brainstem physiology.